Pemetaan Kualitas Udara Kota Surakarta - Kadyarsi, Ibnu (Universitas Muhammadiyah Surakarta, 2006)
Emerging concentration of COx gas as an emision gases that was caused by vehicle will create that air quality degradation in urban area. Air quality mapping was needed as a based map to solved on air quality problem in urban area. The aim of this research are mapping of air quality in Surakarta Municipality and to select the cartographic symbols which optimum to represent of air quality data especially Cox for more readable and analysis. Data collecting based on field survey in some observation point that derived purposively on several roads and dense traffict. Field data plotting on the map are used in some symbols such as pie-graph, bar-graph, and text. The mentioned symbols are usual in cartography to represent of point symbol. The result of this research is distribution map of COx concentration in Surakarta Municipality. The road which has high COx concentration are cross jucntion in downtown (west side of Pasar Klewer), cross junction of Yos Sudarso street, Slamet Riyadi Street, and cross junction of Hay Lay (Wates). The used of pie-graph and bar-graph symbols produce more interesting map visually, but unfortunately the symbols cover up the information in their based map. The used of text symbol is more easy to handle for lay out, so the background object in based map is uncovere, but visually the map is not interesting.